A multi-objective optimization method for aerospace product research and development process based on particle swarm optimization algorithm and critical path algorithm. Issue 1 (January 2021) - Liu, Yan; Yin, Bo; Jia, Dongning
Abstract: In order to realize the multi-objective management objectives in the production cycle of aviation products, this paper combines particle swarm optimization algorithm and critical path optimization algorithm to carry out multi-objective optimization on the research and development process of aviation products. First, calculate the start time of each process by the critical path method and construct the initial population. Then construct the fitness function. Finally, particle swarm optimization is used for optimization, and through continuous iteration, the optimal combination that can achieve multi-objective optimization is obtained. Through the optimization experiment on the research and development process of aviation products, the global optimal research and development process calculated in this paper can shorten the production period by 32.4% and reduce the cost by 41.1%. Therefore, the multi-objective optimization scheme based on hybrid optimization algorithm proposed in this paper has theoretical and practical significance for the model management of the whole life cycle of aviation products.